PENGARUH TEKNOLOGI INFORMASI DAN INSENTIF PADA KINERJA INDIVIDU DIMODERASI PELATIHAN DAN PENGALAMAN KERJA - Artana, I Made Wahyu; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2017)
The productivity of individual performance in government agencies is very important to note. Especially if there is a paradox productifity phenomenon that is expensive investment but produces a low rate of return. Regional Revenue Agency of Badung Regency is required to improve individual performance in local financial management process by applying progress in information technology, incentives, training, work experience and improvement of human resource performance. So it is able to achieve maximum work target in the absorption of local revenue in Badung regency. This study aims to test and provide empirical evidence of variables that are able to strengthen the positive influence of information technology and incentives on individual performance, that is by adding training and work experience as a moderating variable. This study was conducted on the users of information technology in the Regional Revenue Agency of Badung Regency. With the number of sample used counted 60 people by using purposive sampling technique. Methods of data collection were conducted by survey method using questionnaire. Data analysis technique used is Moderating Regression Analysis (MRA). Based on the results of the analysis found that information technology and incentives have a positive effect on individual performance. Training variables and work experience are largely able to reinforce the positive influence of information technology and incentives on individual performance. Only the influence of incentives on individual performance is moderated by rejected work experience. Keywords: Information Technology, Incentives, Training, Work Experience, Individual  Performance